Analysis on the factors related to corporate expenditure on preventing industrial accidents - CHOI, Sunguk (KDI School, 2022)
Public demand for occupational health and safety has increased in South Korea as suggested by a number of legislations that were amended or enacted recently (i.e. amendment to the Korea Occupational Safety and Health Act in 2020, Serious Accidents Punishment Act in 2022). In light of this, the study aims to investigate different factors that could impact firms’ investment toward occupational safety and health. Fixed effect regression using panel survey data from 2015-2019 by South Korea’s Workplace Panel Survey demonstrated that only the number of prior year accidents had a positive and statistically significant association with a firm’s safety investment. Other factors including firm size, firm loss due to industrial accidents, and the fraction of temporary workers showed no statistically significant association with a firm’s investment toward occupational health and safety. Although this study had merit for investigating different factors behind firms’ behavior toward safety investment, further studies may reveal more of this nature especially during some years after the enactment of Serious Accidents Punishment Act
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Industrial safety; Industrial accidents--Law and legislation--Korea (South)